The concept of the global hunger index - von Grebmer, Klaus; Bernstein, Jill; de Waal, Alex; Prasai, Nilam; Yin, Sandra; Yohannes, Yisehac (Welthungerhilfe, 2015)
The Global Hunger Index (GHI) is a tool designed to comprehensively measure and track hunger globally, regionally, and by country.1 Each year, the International Food Policy Research Institute calculates GHI scores in order to assess progress, or the lack thereof, in decreasing hunger. The GHI is designed to raise awareness and understanding of regional and country differences in the struggle against hunger. By calling attention to the issue, we hope that this report will trigger action to reduce hunger around the world.